2020
DOI: 10.1007/s10980-020-01088-4
|View full text |Cite
|
Sign up to set email alerts
|

Conservation significance of intact forest landscapes in the Scandinavian Mountains Green Belt

Abstract: Context As forest harvesting remains high, there is a crucial need to assess the remaining large, contiguous and intact forests, regionally, nationally and globally. Objectives Our objective was to analyze the spatial patterns and structural connectivity of intact and primary forests in northern Sweden with focus on the Scandinavian Mountain region; one of the few remaining large European intact forest landscapes. Methods Over 22 million ha with 14.5 million ha boreal and subalpine forest and with data consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 74 publications
1
43
0
1
Order By: Relevance
“…These results are consistent with previous studies in boreal forests, showing that remnant natural forests are often found in less productive environments (Schröter et al, 2014;Martin et al, 2020a;Sabatini et al, 2020). A steeper topography also often explains the absence of anthropogenic disturbances (Joppa and Pfaff, 2009;Belote and Aplet, 2014;Svensson et al, 2020). We found in the study area the opposite trend, probably because the topography of the boreal landscapes of eastern Canada is relatively smooth and a slightly steeper slope improve stand productivity due to a better drainage (Martin et al, 2018;Laamrani and Valeria, 2020).…”
Section: Divergent Impacts Of Logging Compared To Fire May Threaten Bsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with previous studies in boreal forests, showing that remnant natural forests are often found in less productive environments (Schröter et al, 2014;Martin et al, 2020a;Sabatini et al, 2020). A steeper topography also often explains the absence of anthropogenic disturbances (Joppa and Pfaff, 2009;Belote and Aplet, 2014;Svensson et al, 2020). We found in the study area the opposite trend, probably because the topography of the boreal landscapes of eastern Canada is relatively smooth and a slightly steeper slope improve stand productivity due to a better drainage (Martin et al, 2018;Laamrani and Valeria, 2020).…”
Section: Divergent Impacts Of Logging Compared To Fire May Threaten Bsupporting
confidence: 92%
“…Previous research has mainly focused on changes in landscape age structure and/or tree composition (Östlund et al, 1997;Cyr et al, 2009;Boucher et al, 2017a). Others observed a posteriori if protected and/or unmanaged forests were representative of the surrounding areas (Lõhmus et al, 2004;Joppa and Pfaff, 2009;Svensson et al, 2020). Stands of a similar age-class and tree composition can, however, be defined by different structural characteristics and may provide different habitats for biodiversity (Rheault et al, 2009;Martin et al, 2018).…”
mentioning
confidence: 99%
“…A non-exhaustive compilation of datasets (32 in total), produced from local, regional, and national-scale inventories were included in the Supplementary Material of Sabatini et al, (2018). Local and regional studies have commonly focused on protected areas such as national parks (Blasi et al, 2010) and regions known to host a substantial portion of Europe's primary forests such as the Carpathians (Svoboda et al, 2014;, the Northern Pyrenees (Savoie et al, 2015), Northern Europe (Svensson et al, 2020), or certain forest types such as beech (UN-ESCO, 2011; Kirchmeir et al, 2016). Only a small number of national-scale inventories have been completed and published (Sabatini et.…”
Section: Mapping Primary and Old-growth Forests In Europementioning
confidence: 99%
“…In northern Europe, large intact forest landscapes are only found on the Swedish side of the Scandinavian mountain range, the forest border area between Finland and Northwest Russia, and the Kola peninsula forest belt [32]. Elsewhere in the region, most forests were systematically transformed into plantation forests [33]. Intact forest landscapes and primary forests were lost, and the remaining patches are highly fragmented, with the effects of fragmentation even further pronounced when edge effects are considered [34].…”
Section: Introductionmentioning
confidence: 99%